Risk factors for complications after laparoscopic major hepatectomy. Issue 3 (17th December 2014) - Nomi, T; Fuks, D; Govindasamy, M; Mal, F; Nakajima, Y; Gayet, B
Abstract: Background: Although laparoscopic major hepatectomy (MH) is becoming increasingly common in several specialized centres, data regarding outcomes are limited. The aim of this study was to identify the risk factors for postoperative complications of purely laparoscopic MH at a single centre. Methods: All patients who underwent purely laparoscopic MH between January 1998 and March 2014 at the authors' institution were enrolled. Demographic, clinicopathological and perioperative factors were collected prospectively, and data were analysed retrospectively. The dependent variables studied were the occurrence of overall and major complications (Dindo–Clavien grade III or above). Results: A total of 183 patients were enrolled. The types of MH included left-sided hepatectomy in 40 patients (21·9 per cent), right-sided hepatectomy in 135 (73·8 per cent) and central hepatectomy in eight (4·4 per cent). Median duration of surgery was 255 (range 100–540) min, and median blood loss was 280 (10–4500) ml. Complications occurred in 100 patients (54·6 per cent), and the 90-day all-cause mortality rate was 2·7 per cent. Liver-specific and general complications occurred in 62 (33·9 per cent) and 38 (20·8 per cent) patients respectively. Multivariable analysis identified one independent risk factor for global postoperative complications: intraoperative simultaneous radiofrequency ablation (RFA) (odds ratio (OR) 6·93, 95 per cent c.i. 1·49 to 32·14; P = 0·013). There were two independent risk factors for major complications: intraoperative blood transfusion (OR 2·50, 1·01 to 6·23; P = 0·049) and bilobar resection (OR 2·47, 1·00 to 6·06; P = 0·049). Conclusion: Purely laparoscopic MH is feasible and safe. Simultaneous RFA and bilobar resection should probably be avoided. Abstract : Careful with bilobar resections